Tenascin-C can Serve as an Indicator for the Immunosuppressive Microenvironment of Diffuse Low-Grade Gliomas - Zhang, Po; Liu, Guohao; Hu, Jinyang; Chen, Sui; Wang, Baofeng; Peng, Peng; Yu, Xingjiang; Guo, Dongsheng (Frontiers in Immunology, 2022)
Purpose: The development and progression of glioma are associated with the tumor immune microenvironment. Diffuse low-grade gliomas (LGGs) with higher immunosuppressive microenvironment tend to have a poorer prognosis. The study aimed to find a biological marker that can reflect the tumor immune microenvironment status and predict prognosis of LGGs. Methods: The target gene tenascin-C (TNC) was obtained by screening the Chinese Glioma Genome Atlas (CGGA) and the Cancer Genome Atlas (TCGA) databases. Then samples of LGGs were collected for experimental verification with immunohistochemistry, immunofluorescence, immunoblotting, quantitative real-time PCR. ELISA was employed to determine the content of TNC in serum and examine its relationship with the tumor immune microenvironment. Eventually, the sensitivity of immunotherapy was predicted on the basis of the content of TNC in LGGs. Results: In the high-TNC subgroup, the infiltration of immunosuppressive cells was increased (MDSC: r=0.4721, Treg: r=0.3154, etc.), and immune effector cells were decreased (NKT, γδT, etc. (p<0.05)) , immunosuppressive factors were elevated (TGF-β, IL10, etc. (p<0.05)), immunostimulatory factors, such as NKG2D, dropped (p<0.05), hypoxia scores increased (p<0.001), and less benefit from immunotherapy (p<0.05). Serum TNC level could be used to assess the status of tumor immune microenvironment in patients with grade II (AUC=0.8571; 95% CI: 0.6541-1.06) and grade III (AUC=0.8333; 95% CI: 0.6334-1.033) glioma. Conclusions: Our data suggested that TNC could serve as an indicator for the immunosuppressive microenvironment status and the prognosis of LGGs. Moreover, it could also act as a predictor for the effect of immunotherapy on LGG patients.